The Influence of Competence and Compensation on Performance Through the Mediation of Satisfaction in Traditional Villages in Denpasar City - I Wayan Agus Purnawirawan; I Gede Wirata; Ida Ayu Putu Sri Widnyani (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The Bali Provincial Regional Regulation Number 4 of 2019 on Customary Villages in Bali and Number 4 of 2022 on the Guidelines for the Establishment of the Village-Owned Business Entity (BUPDA) are strategic steps to strengthen the role of Customary Villages in local wisdom-based economic development. One of the implementations is the establishment of BUPDA as a business unit owned by the Customary Village. However, based on data from the Bali Customary Community Advancement Office (2022), out of 35 Customary Villages in Denpasar City, only 8 villages (23%) have established BUPDA. This condition reflects the suboptimal performance of Customary Villages in Denpasar City. This study uses a quantitative approach with a causal associative method to test the influence of competence, compensation, and satisfaction on the performance of Customary Village administrators (prajuru) in Denpasar City. Data were collected from 140 prajuru through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The aim of this study is to evaluate the extent to which each variable influences the performance of the prajuru and to understand the role of satisfaction as a mediator in the relationship between competence, compensation, and performance. The research findings show that competence, compensation, and satisfaction have a positive and significant influence on the performance of Customary Village prajuru. Job satisfaction was also found to be a significant mediator in the relationship between competence and compensation on performance. These findings highlight the importance for Customary Villages in Denpasar City to continuously improve the competence of prajuru through training and capacity building, as well as ensure a fair, transparent, and performance-based compensation system to enhance job satisfaction. This study recommends that institutional strengthening be carried out not only from the human resources side but also through improvements in work systems and the development of the economic aspects of the customary village, including the establishment of Village-Owned Business Entities (BUPDA) as a strategic effort to improve performance and the sustainable well-being of the customary community.